Non-Linear Association Between Serum Alkaline Phosphatase and 3-Month Outcomes in Patients With Acute Stroke: Results From the Xi'an Stroke Registry Study of China - Guo, Weiyan; Liu, Zhongzhong; Lu, Qingli; Liu, Pei; Lin, Xuemei; Wang, Jing; Wang, Yuanji; Chang, Qiaoqiao; Wang, Fang; Wu, Songdi (Frontiers in Neurology, 2022)
Background Alkaline phosphatase (ALP) is associated with an increased risk of cardiovascular events and is closely related to adverse outcomes after stroke. However, the regional investigation into the associations of ALP with acute stroke (AS) outcomes is limited. This study aimed to identify the association between serum ALP levels and clinical outcomes 3 months after AS in the Xi'an district of China. Methods We enrolled all patients with AS from 4 hospitals in the Xi'an district from January to December 2015. ALP levels and related patient information were collected at admission, and the events of stroke outcomes were followed up 1 and 3 months after diagnosis. ALP levels were analyzed as continuous variables and quartiles (Q1–Q4). The outcomes included all-cause mortality, recurrent stroke, and poor functional outcomes (modified Rankin Scale score of 3–6) within 3 months. A multivariate logistic regression and interaction analyses were performed to evaluate the independent association between serum ALP level and 3-month stroke outcomes. Results Overall, 2,799 patients with AS were enrolled in this study. The mean age was 63.9 ± 12.5 years. In the Q4 (≥93.0 U/L) group, the incidences of all-cause mortality, recurrent stroke, and poor functional outcomes were 7.8, 2.7, and 24.9%, respectively. After being adjusted for confounding variables, patients in Q4 (≥93.0 U/L) were related to an increased risk of all-cause mortality [odds ratio (OR) = 2.17, 95% CI: 1.19–3.96; P = 0.011] and patients in Q3 (76.8–92.9 U/L) were related to a lower risk of recurrent stroke (OR = 0.37, 95% CI: 0.14–0.97; P = 0.043) at the 3-month time point, compared to those in Q2 (63.0–76.7 U/L). The optimal range of ALP for all-cause mortality was seen in Q2, with a nadir level of 70 U/L. However, differences were statistically insignificant between ALP levels and poor functional outcomes (P > 0.05). Moreover, there was no significant interaction between ALP levels and age, gender, drinking status, smoking status, or pneumonia (P > 0.05) for all outcomes. Conclusion Non-linear associations were observed between serum ALP levels and 3-month outcomes in patients with AS. It might be beneficial to reduce the risk of all-cause mortality and recurrent stroke by maintaining ALP at optimal ranges.